1992
DOI: 10.1063/1.1142948
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dc, broad beam, Mevva ion source

Abstract: We are developing an embodiment of metal vapor vacuum arc (Mevva) ion source which will operate dc and have a very large area beam. In preliminary testing, a dc titanium ion beam was formed with a current of approximately 0.6 A at an extraction voltage of 9 kV (about 18 keV ion energy, by virtue of the ion-charge state distribution) using an 18-cm-diameter set of multiaperture extraction grids. Separately, we have tested and formed a beam from a 50-cm-diameter (2000 cm2) set of grids using a pulsed plasma gun.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Still the results are very encouraging, suggesting extrapolation to a high current device should be possible. To provide some feeling for the performance of this new ion source we compared its key characteristics to a wide variety of other types of ion sources, based on four key articles (Fitch, 1971;Lobanov, 1994;Brown, 1992;Takahashi, 1996). It was found that the magnetic-index approach in the ILLIBS configuration exhibits several advantages over other ion gun designs: simpler design, higher extraction efficiency; 10 ((mA/cm 2 )/W), lower divergence; 10.8 ± 0.36 mrad, and a very intensive ion flux; 6 x 10 18 ions/(cm 2 .sec) measured at 0.27 Pa.…”
Section: Discussionmentioning
confidence: 99%
“…Still the results are very encouraging, suggesting extrapolation to a high current device should be possible. To provide some feeling for the performance of this new ion source we compared its key characteristics to a wide variety of other types of ion sources, based on four key articles (Fitch, 1971;Lobanov, 1994;Brown, 1992;Takahashi, 1996). It was found that the magnetic-index approach in the ILLIBS configuration exhibits several advantages over other ion gun designs: simpler design, higher extraction efficiency; 10 ((mA/cm 2 )/W), lower divergence; 10.8 ± 0.36 mrad, and a very intensive ion flux; 6 x 10 18 ions/(cm 2 .sec) measured at 0.27 Pa.…”
Section: Discussionmentioning
confidence: 99%
“…We've made several broad beam source versions, including our 10-cm "workhorse" source that we use for our routine ion implantation work [5,16], a 20-cm source that we used to test d.c. ion 5 beam extraction [5,17,18], and a source having a 50 cm diameter (2000 cm2) extractor 15,181. A photograph of the very large area extractor grids is shown in Figure 1.…”
Section: Very Large Area Beam Productionmentioning
confidence: 99%
“…Broad beam operation is advantageous because of its simplicity. The essential feature of this kind of ion source is that the plasma is allowed to expand to large size prior to beam formation, preferably in a configuration such that the transverse plasma density distribution, and hence also the ion beam current profile, is relatively flat.We've made several broad beam source versions, including our 10-cm "workhorse" source that we use for our routine ion implantation work [5,16], a 20-cm source that we used to test d.c. ion 5 beam extraction [5,17,18], and a source having a 50 cm diameter (2000 cm2) extractor 15,181. A photograph of the very large area extractor grids is shown in Figure 1.…”
mentioning
confidence: 99%
“…Large source embodiments [2,6], on the other hand, call for well-designed water cooling if the beam current is to be as large as it can be. If a multi-cathode design is to be used, the concern of accomplishing good cooling of the multiple cathode assembly while retaining its freedom to rotate requires some careful thought.…”
mentioning
confidence: 99%
“…-A DC suwce has been made and tested [2,6]. For steady state operation, very good cooling is required of both the gun assembly (anode and cathode) as well as the extractor.…”
mentioning
confidence: 99%